2022
DOI: 10.1097/iae.0000000000003318
|View full text |Cite
|
Sign up to set email alerts
|

Altmetric Analysis of the Most-Cited 100 Articles on the Retina Published Between 2010 and 2020

Abstract: Purpose: Altmetric analysis is a way of assessing the social impact of scientific articles. In this study, we aimed to analyze the 100 most-cited articles on the topic of the retina published in ophthalmology journals in traditional metrics and altmetrics.Methods: The term "retina" was searched in the Web of Science database, and articles published in ophthalmology journals were filtered out. A total of 100 highly cited articles from 2010 to 2020 were evaluated for bibliographic data and altmetrics. First, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…83 A second study of the 100 most cited articles on retinal diseases published from 2010 to 2020 showed no correlation between score and citation number, and weak correlation with impact factor. 84 These findings are not unexpected, as recency and general publicity do not factor into traditional impact metrics. Another study on glaucoma involved articles selected by Altmetric Attention Score: articles on medical treatment were associated with significantly higher scores, and those that reported modifiable glaucoma risk factors attracted particularly high-online interest.…”
Section: Medical Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…83 A second study of the 100 most cited articles on retinal diseases published from 2010 to 2020 showed no correlation between score and citation number, and weak correlation with impact factor. 84 These findings are not unexpected, as recency and general publicity do not factor into traditional impact metrics. Another study on glaucoma involved articles selected by Altmetric Attention Score: articles on medical treatment were associated with significantly higher scores, and those that reported modifiable glaucoma risk factors attracted particularly high-online interest.…”
Section: Medical Researchmentioning
confidence: 97%
“…In one study related to glaucoma, the score of the 50 most highly cited papers published between 2009 and 2019 showed moderate correlation with citation number, and no correlation with journal impact factor 83 . A second study of the 100 most cited articles on retinal diseases published from 2010 to 2020 showed no correlation between score and citation number, and weak correlation with impact factor 84 . These findings are not unexpected, as recency and general publicity do not factor into traditional impact metrics.…”
Section: Applications Of Social Media In Ophthalmic Education Trainin...mentioning
confidence: 99%
“…The fact that case reports with a low level of scientific evidence compared to others have such a high AAS can be considered a result of the popularity of a disease affecting the public. In the study in which retinal articles in ophthalmology journals were evaluated, it was found that an article on retinal complications of Zika virus had the highest AAS [ 11 ]. In a study in which an altmetric analysis of 100 articles related to COVID-19 was performed, it was reported that the AAS was 3246 ± 3795 (85-16548) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ophthalmology, studies have demonstrated a weak to moderate correlation between the AAS and conventional metrics such as the number of citations and H-index. (11)(12)(13) A recent study showed that publications that are promoted on Twitter end up having a higher number of citations than the ones with no tweets. (14) In a study looking into publications from a different specialty (cardiology), Twitter promotion was linked with a 1.12 higher citation rate.…”
mentioning
confidence: 99%